Navigating the Politics of Space: Critical Anthropological Perspectives on Sustainable Palm Oil Spatial Planning in Indonesia - Judijanto, Loso (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Indonesia's palm oil sector faces a fundamental paradox between its significant economic contribution to development and community welfare and its substantial socio-ecological impacts, such as deforestation, land conflicts, and spatial injustice. This study aims to analyze the challenges in implementing sustainable palm oil spatial planning through a critical anthropological approach. The method used is a qualitative literature review with thematic synthesis of various scientific studies, policy documents, and recent empirical studies. The research results identified five main challenges, namely the process of technicization that depoliticizes agrarian conflicts, the mismatch of scale between administrative boundaries and socio-ecological systems, the contestation between state-planned spaces and spaces lived by communities, spatial injustice in distributive, procedural, and recognition dimensions, as well as governance fragmentation. The findings indicate that the technocratic approach in spatial planning risks becoming an instrument that conceals structural issues and maintains inequalities, including the marginalization of indigenous community rights. Therefore, a more inclusive, integrated, and spatial justice-based spatial planning approach is needed, emphasizing the recognition of rights, community participation, and cross-scale and sectoral coordination to achieve sustainability that is not only focused on ecological aspects but also social and intergenerational justice.